Deictic Features of Verbs in French and Uzbek Languages - Ishanjanova Munosibxon Saidahmadovna (Zien Journals, 2022)
This article covers the spatial deictic features of verbs in French and Uzbek on the basis of examples. Also, models describing their position in sentences are formed and analyzed similar and nonsimilar aspects in both languages.
Keywords: local action; prepositions